The sound effects bible : how to create and record Hollywood style sound effects - Viers, Ric (Michael Wiese Productions, 2008)
The Sound Effects Bible is a complete guide to recording and editing sound effects. The book covers topics such as microphone selection, field recorders, the ABCs of digital audio, understanding Digital Audio Workstations, building your own Foley stage, designing your own editing studio, and more.